Students’ Perception of Using Mondly German as a Learning Media, A Case Study of Sixth Semester Students of German Language Education - Irma Liani; Cahaya Mustika; Greace Simaremare; Teresia Fatmawati Simangunsong; Binti Aisiah Daning Sumari; Fitri Ervina Tarigan (AR-RUMMAN: Journal of Education and Learning Evaluation, 2026)
This study aims to explore students' perceptions of using the Mondly German application as a medium for learning German to support independent learning outside the classroom. The research background stems from the need for innovative learning approaches among Semester VI students in the German Language Education Program at Universitas Negeri Medan, who are accustomed to formal classroom methods, while Mondly German offers interactive features such as conversation exercises, grammar drills, and vocabulary games. Employing a descriptive quantitative method, data were collected via a System Usability Scale (SUS)-based questionnaire from 30 students and analyzed through SUS calculations (stages 1–4) along with validity testing. The results revealed an average SUS score of 79.13 (grade C, excellent category, high acceptability level), with all questionnaire items deemed valid (r > r-table). It is concluded that students hold positive perceptions of Mondly German, suggesting that the application can serve as a supportive medium for German language learning. Theoretically, this finding supports the integration of technology-based learning tools in second language acquisition and contributes to the understanding of student attitudes toward interactive language apps. Practically, educators and curriculum developers can consider incorporating Mondly German as a supplementary resource to enhance independent learning and student engagement.